Application of Fungal Waste Biomass Originating from Steroid Hormone Manufacture for Heavy Metals Removal - Paraszkiewicz, Katarzyna; Felczak, Aleksandra; Długoński, Jerzy (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2009)
The biomass of Curvularia lunata, used previously for hydrocortisone production, was investigated as a heavy metal biosorbent. Removal of lead, zinc and cadmium ions was evaluated as a function of biosorbent dosages, initial ion concentrations, mode of mycelium modifications, initial pH of metal solutions and when these metals ions where presented in binary as well in ternary combinations. The results presented in this paper indicate the potential utility of C. lunata waste biomass for lead and, to a lower extent, for zinc and cadmium ions removal from acid solutions.